APLIKASI PUPUK ORGANIK CAIR (POC) URIN KELINCI DAN ASAP CAIR TEMPURUNG KELAPA TERHADAP PERTUMBUHAN TANAMAN SELADA KERITING (LACTUCA SATIVA VAR. CRISPA) - Nawaf Hanifa, Arrya
Curly lettuce (Lactuca sativa var. crispa), one of the consumption leaf vegetables, has a high demand and a wide open market. Lettuce cultivation still uses chemical fertilizers. The community began to be aware of the negative impact of chemicals and was more selective in choosing products for consumption. Chemical fertilizers and pesticides leave residues that have a negative impact on the environment and human health. The market responds to consumer demand and set organic product standards. Organic agricultural trends arise which also have the consequences of increasing the need for fertilizer that must be organic. Organic fertilizer can be made from rabbit urine as Liquid Organic Fertilizer (LOF) and smoke from making biochar. But both do not have a good concentration reference to be used specifically for curly lettuce. This study aims to determine the best concentration of rabbit urine liquid organic fertilizer and coconut shell liquid smoke on the growth of curly lettuce plants (Lactuca sativa var. crispa). The study used a Randomized Complete Block Design group (RCBD) with treatments A (0 mL L-1 LOF, 0 mL L-1 of liquid smoke), B (20 mL L-1 LOF, 0 mL L-1 liquid smoke), C (40 mL L-1 LOF, 0 mL L-1 liquid smoke), D (0 mL L-1 LOF, 10 mL L-1 liquid smoke), E (0 mL L-1 LOF, 20 mL L-1 liquid smoke), F (20 mL L-1 LOF, 10 mL L-1 liquid smoke), G (20 mL L-1 LOF, 20 mL L-1 liquid smoke), H (40 mL L-1 LOF, 10 mL L-1 liquid smoke), I (40 mL L-1 LOF, 20 mL L-1 liquid smoke). The results showed the treat of 20 mL L-1 of LOF rabbit urine and 10 mL L-1 of liquid smoke was the best concentration on plant height parameter, number of leaves, width of leaves, wet weight, and shoot root ratio of curly lettuce plants.